Research of Category "Motivation" as a Basic Tool of Personnel Management - Koryakovtseva, Olga A.; Doronina, Iuliia I.; Panchenko, Tatiana M.; Karabulatova, Irina S.; Abdullina, Zishana M. (International Review of Management and Marketing, 2016)
According to authors such as P.V. Zhuravlev, Yu.G. Odegov, S.V. Shekshnia, T.S. Solomandina, complex model of Porter - Lawler is the best among the procedural theory, which argues that the motivation is not a simple element in the chain of causality. It is within a single system integrates a large number of concepts (effort, ability, results, compensation, satisfaction and perception). However, it appears that the limitation in this theory is still present. The theory is based on the principle of complexity that is not fully realized because the model does not reflect factors such as the needs, interests, and others. From domestic developments in the field of motivation is best known typological concept of Gerchikova. It focuses on issues of stimulating effective work performance. The concept is based on the idea of the author of motivation, as the prevailing (and therefore not situational, stable) and perceived human motivations that determine the behavior of his labor. Keywords: personnel management, motivation, incentives, efficiency of the enterprise JEL Classifications: D61, M12, P13